An investigation of the antidepressant‐like effect of Jiaotaiwan in rats by nontargeted metabolomics based on ultra‐high‐performance liquid chromatography quadrupole time‐of‐flight mass spectrometry. Issue 2 (27th November 2020) - Jiao, Ziyi; Zhao, Huan; Huang, Wei; Liang, Ru; Liu, Yijia; Li, Zhu; Li, Lin; Xu, Yilan; Gao, Shuming; Gao, Shan; Li, Yubo; Yu, Chunquan
Abstract: Depression is a mental disorder characterized by persistent unhappiness, lack of interest, with cognitive and sleep disorders. Jiaotaiwan is a traditional Chinese medicine for the treatment of insomnia and depressive‐like symptoms. In this study, the major chemical components in Jiaotaiwan were qualitatively analyzed using ultra high performance liquid chromatography quadrupole time‐of‐flight mass spectrometry, and a model of depression in rats was subsequently established with chronic unpredictable mild stress followed by Jiaotaiwan intervention. Next, the metabolic profile of rat serum samples was analyzed using nontargeted metabolomics, wherein changes in the metabolites in serum samples before and after Jiaotaiwan administration were measured by multiple statistical approaches. Principal component analysis and partial least squares discriminant analysis indicated that the Jiaotaiwan treatment improved the metabolic phenotype depression. Moreover, the heatmap analysis identified the most important ten biomarkers involved in depression. According to the pathway analysis, the therapeutic effect of Jiaotaiwan on depression may involve the regulation of amino acid metabolism, glycerophospholipid metabolism, and energy metabolism. These findings help us understand the pathogenesis of depression in‐depth, and discover targets for clinical diagnosis and treatment. And it also lays a foundation for the use of Jiaotaiwan as an antidepressant agent.